Language intellectualization in new media: evolution of genre paradigm - Дергач, Дмитро Валерійович (Київський національний університет імені Тараса Шевченка, 2025)
The article verbalizes author's position, concerning the intellectualization of genre system of media communication (as a result of communication forms' changes in modern society) and determines the criteria for its professional analysis. These are linguistic, functional and stylistic, linguocultural and sociolinguistic dimensions of evolution of forms of social communication in mass-media sphere. The research focuses on the non-specific communicative principles of the dynamics of genres in traditional and new media, that, according to extra- and intralinguistic factors, provide different ways of fulfilling the tasks of communicative situation. The paper states actual nowadays medialinguistic aspectology for research of media genres in projection on language functions, realized in communicatively changing mass-media context, associated with psychological time and space of culture. Particular attention is paid to the dynamics of functional markers in genre paradigm of media space through the language and cognitive integration of new / traditional genres (post, comment, stories, giveaway, etc.), that in their functional combination form a macrotext, relevant for media communication nowadays. The author also touches upon discussion issues of modern communicative linguistics and media genre theory, that outline the prospects for further investigations in this scientific field: accuracy of nomination and status of certain genres, relevance / irrelevance of traditional for stylistics of the 2nd half of the 20th century genre factors – according to the modern genres of media communication, the diffuse nature of the intellectualization of mass media genre system, connected with appropriate / inappropriate differentiation of such categories, as hyper-genre, sub-genre, genre variety unit, etc.

У статті вербалізовано авторську позицію щодо інтелектуалізації мови й жанрової системи сучасної медійної комунікації та визначено актуальні критерії її фахового аналізу. Йдеться, передусім, про лінгвістичний, функціонально-стилістичний, лінгвокультурологічний і соціолінгвістичний виміри еволюції форм суспільної комунікації в масмедіа. Дослідження зосереджено на особливих принципах динаміки жанрів традиційних і нових медіа, які за екстра- та інтралінгвістичними факторами спираються на різні способи виконання завдань комунікативної ситуації, а отже, й добір мовних одиниць, що виконують варіативні функції. Проаналізовано актуальну на сьогодні медіалінгвістичну аспектологію дослідження жанрів ЗМІ у проєкції на функції мови, що вербалізуються в комунікативно змінному контексті сучасних масмедіа, пов'язаному з психологічним часом і простором культури. Особлива дослідницька увага приділяється динаміці функціональних маркерів у жанровій парадигмі медіапростору через мовну та когнітивну інтеграцію нових і традиційних жанрів (допис, коментар, сторіз, гівевей та ін.), які у своєму функціональному поєднанні утворюють макротекст, релевантний для медійної комунікації сьогодні. Автор також порушує дискусійні питання сучасної медійної жанрології, що окреслюють перспективи подальших досліджень у цій науковій галузі: точність номінації та статус окремих жанрів, актуальність / неактуальність традиційних для стилістики 2-ї половини XX ст. жанротвірних чинників. Відповідно до природи частотних сьогодні жанрів медійної комунікації, у свою чергу, проаналізовано дифузний характер жанрової парадигми ЗМІ, пов'язаний із доцільністю / недоцільністю диференціації таких категорій, як гіпержанр, субжанр, жанрова одиниця, міжжанрове утворення та ін.
Інтелектуалізація мови нових медіа: еволюція жанрової парадигми
Keywords: media; new media; media communication; media genre; language function; intellect; intellectualization; медіа; нові медіа; медійна комунікація; медійний жанр; функція мови; інтелект; інтелектуалізація